The Development of a Care Model for Sarcopenic Obesity in Older Adults: Participatory Action Research. - Samaisong, Nuchthida; Somprasert, Chomchuen; Pawloski, Lisa (Nursing Reports, 2025)
Background/Problem: Sarcopenic obesity (SO) is characterized by significant muscle loss combined with obesity, and it is mostly prevalent among older adults. Consequences include a heightened incidence of falls and a greater susceptibility to non-communicable diseases. Thailand currently lacks a care model for SO in older adults. Objective/Purpose: This study utilizes participatory-action research (PAR) to develop a care model for sarcopenic obesity in Thailand. Design and Methodology: In-depth interviews with 25 older adults with SO and focus group discussions with 12 stakeholders were conducted to develop a preliminary care model. An action research spiral process was utilized with 15 older adults with SO over 16 weeks. Findings: We developed a culturally sensitive care model for SO in older adults. This study demonstrates that a participatory-action research (PAR) method for behavior transformation, highlighting health awareness and SO literacy, is crucial for behavior change. Conclusions and Implications: The behavior change process using transformative behaviors facilitated internal changes. This approach helps individuals to understand interconnected factors through personal experiences, leading to profound understanding and readiness for deep, continuous, and meaningful behavioral changes.